Outcome Analysis of Hip Arthroscopy (Journal of Pakistan Orthopaedic Association, 2013)
Hip arthroscopy has evolved significantly over last two decades. Many procedures are being done arthroscopically as our understanding increases. However, in many countries, including Pakistan, Hip arthroscopy is in its infancy. We present our outcome of Hip arthroscopy. To the best of our knowledge this is the first report of outcome after hip arthroscopy in our local literature.Material and Methods: We prospectively reviewed our first sevenconsecutive hip arthroscopy patients. The outcome was measured using modified Haris Hip score. The common indications in our set up were: septic hip (primary and post THR) and synovial pathology.Results: Out of seven patients one lost to follow up. Of the remaining sixpatients, four had hip infection. One of these cases was post Total Hip Replacement. In two patients hip arthroscopy was done for synovial pathology.In all the patients with septic arthritis, there was significant improvement – mean preop modified Harris hip score was 33.1(range 24-43) which increased to 56.8 (Range 29-71) after debridement except one patient with infected THR. The mean follow up of these patients is 6.6 months( range3-10 months). Mean length of hospital stay was 2.6 days (range 1-4) Two patients developed transient neuropraxia which resolved spontaneously.Conclusion: Hip arthroscopy is a promising technique in selected patients with major advantages of reduced surgical trauma and excellent 360 degrees visualization of joint and shorter hospital stay . However, there is a steep learning curve. With careful portal placement and appropriate skills, hip arthroscopy has minimized the surgical trauma to access to hip joint.